From Soapstone Quarries to Churches: Control, Ownership and Transport Along the Helgeland Coast in North Norway - Berglund, Birgitta; Heldal, Tom; Grenne, Tor (UBAS Universitetet i Bergen, 2017)
Several soapstone quarries are found along the coast of Helgeland in north Norway, including some on islands in the mouth of Vefsnfjorden, where there are significant ancient workings. Several medieval stone churches in the area are built of soapstone. Soapstone vessels are found in grave mounds from the Viking Age. In farm mounds, everyday utensils and rough-outs made from soapstone are commonly found. The most important quarries are briefly presented here, along with the soapstone churches. Provenance studies are used to determine from which quarries the soapstone used in the churches came. The results indicate that such studies may tell us much about the ownership and control of the quarries, the distribution of soapstone for building purposes, the builders of the churches and aspects related to the production and quarrying of soapstone used for building purposes. publishedVersion Published by UBAS Universitetet i Bergen. Under a CC BY-NC-SA 4.0 license.